Evaluating the effect of methotrexate on the rate of renal fibrosis by elastography and fibrosis-related gene expression - Wang, ZiFan; Ab Hamid, Suzana; Jiang, YanSheng; Shang, XiaoBin; Fu, Zhuo; Zhao, QingJiang; Ab Hamid, Suzana (Cellular and Molecular Biology, 2022)
Methotrexate is mainly used to treat diseases such as rheumatoid arthritis (RA), but its potential for nephrotoxicity has always been a significant concern on the use of this medication. This study aimed to determine the rate of renal fibrosis using transient elastography and its relationship with cumulative dose and duration of drug use in patients with rheumatoid arthritis treated with methotrexate. TGFβ gene expression was also assessed for further evaluation. Patients with rheumatoid arthritis who received methotrexate for more than six months were included. Renal fibrosis was determined by measuring the stiffness of the kidney by elastography (FiberScan Device). RA patients were divided into two groups based on kidney stiffness measurement with and without renal fibrosis, and demographic, clinical, and biochemical parameters were compared to investigate the relationship between cumulative dose and duration of methotrexate treatment and renal fibrosis. Also, in this study, 50 controls (healthy people) and 50 cases (RA patients) were used to evaluate the expression of the TGFβ gene by real-time PCR method. The existence of kidney fibrosis was observed in 10 patients. There was no significant relationship between renal fibrosis and the cumulative dose (P = 0.21) and duration of methotrexate (P = 0.30). Multivariate regression analysis showed that the chances of developing renal fibrosis in patients increase with increasing serum ALT levels (P = 0.01). The results of the TGFβ gene expression showed that the expression of this gene in the group of RA patients with fibrosis was higher than the control group (healthy people) and the group of RA patients without fibrosis (P <0.01). These results showed that evaluation of renal fibrosis by elastography method is recommended for scanning RA patients while they are being treated with methotrexate, which is also confirmed by the results of the fibrosis-related-gene expression.